Microbial diversity and microbiological quality of edible-birdnest (EBN) during processing and storage - Zuber, Shazreena; Zakaria, Zunita; Abu, Jalila; Abdul Aziz, Saleha (Chulalongkorn University, Faculty of Veterinary Science, 2022)
The microbial quality of 45 EBN consisting of raw unclean and raw clean Edible-birdnest (EBN) from two different premises were analyzed for 8 weeks. Using 3M™ Petrifilm, Total Aerobic Count (TAC) of raw clean EBN and Total Coliform Count (TCC) for raw unclean, 3 days, 2 weeks and 4 weeks EBN in both premises exceeded the limit stated in by the Malaysian Standard (MS 2334:2011; SIRIM/DVS 3:2015). A total of 264 bacteria and 208 fungi species were isolated. Bacteria isolated was identified using bioMérieux’s API® kit and a series of biochemical tests. Fungi were identified using techniques described by the techniques of James and Natalie (2001). The most common bacteria encountered in both premises were Staphylococcus sp., Corynebacterium sp. and Actinomyces sp. While in premise B, Aeromonas sp. and Ochrobactrum anthropi were also found to be prevalent. The difference in occurrence of bacteria in EBNs in both premises at all stages were found to be non-significant (P>0.05). As for fungi, Aspergillus niger was the most encountered fungi in premise A. While in premise B, Candida sp. was the most frequently isolated in that premise. The most common fungi encountered in both premises were Aspergillus niger and Mucor sp. Differences in occurrence of the fungi were only significant in the raw unclean EBN and non-significant in the rest of the stages. The bacteria and fungi mostly found in this study were environmental microorganisms. In one of the premise practices, Good Manufacturing Practice (GMP), however the results indicate that the cleaning process of both premises are similar as the source of contamination could be caused by mishandling, cleaning, processing step and equipment.